2011
DOI: 10.1111/j.1464-410x.2011.10512.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of surgical treatments for benign prostatic hyperplasia and presentation of an approach to investigate therapeutic equivalence (non‐inferiority)

Abstract: Study Type – Therapy (systematic review) Level of Evidence 1a What's known on the subject? and What does the study add? Numerous newer (non‐standard) procedures for the treatment of benign prostatic hyperplasia (BPH) exist; however, it is unclear whether they actually have an additional patient‐relevant benefit compared to standard treatment. As no trial investigated non‐inferiority, we defined a non‐inferiority threshold on the basis of published literature. The present systematic review found no proof of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In a recent systematic review it was not clear if the new techniques have actual patient related benefits over the standard treatment in symptom score reduction. 18 However, Wilson et al reported an equivalent symptom score reduction for HoLEP and TURP with superior urodynamic outcomes after HoLEP. 5 The noninferiority of 120 W GreenLight PVP to TURP in reducing LUTS at 1 year was not confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent systematic review it was not clear if the new techniques have actual patient related benefits over the standard treatment in symptom score reduction. 18 However, Wilson et al reported an equivalent symptom score reduction for HoLEP and TURP with superior urodynamic outcomes after HoLEP. 5 The noninferiority of 120 W GreenLight PVP to TURP in reducing LUTS at 1 year was not confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…10 In any case, the three types of procedures are still far from reaching a worldwide acknowledgement as standard alternatives within the therapeutic armamentarium of large BPH cases. 11 To the best of our knowledge, the present analysis constitutes the first report analyzing the bipolar endoscopic resection, vaporization, and enucleation of high-volume prostates within a unitary clinical setting emphasizing a prospective, randomized controlled comparison to open surgery. The primary endpoint of this study was to provide an evidence-based parallel between the three types of techniques using the same cutting current and technological setup and the standard OP in terms of perioperative safety profiles, BPH tissue ablation capabilities, and medium-term functional outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…In recent decades, many surgical methods have been developed for treating BPH 3 . So far, transurethral resection of the prostate (TURP) is considered to be the gold-standard treatments of BPH 4 .…”
Section: Introductionmentioning
confidence: 99%